ANALYSIS OF SCIENCE PROCESS SKILLS OF STUDENTS IN GRADE V SD MUHAMMADIYAH KUTOARJO - Suwardi, Dheliana (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
The type of research used in this research is descriptive qualitative research. The research subjects were fifth grade students of Muhammadiyah Kutoarjo Elementary School in the 2023/2024 academic year with a total of 6 students based on high, medium, and low cognitive abilities. Data collection techniques in this study used observation, interviews, questionnaires, and documentation. The results of this study are: Science process skills of grade V students of SD Muhammadiyah Kutoarjo are proficient, which include, 1) Observing science process skills are feasible and proficient, with a total of 4 students who have reached the indicator. 2) The science process skills of predicting indicators are newly developed, feasible, and newly developed, with a total of 2 students who have reached the indicator. 3) The science process skills of the classifying indicator are newly developed, feasible, and, proficient, with a total of 4 students who have reached the indicator. 4) The science process skills of the interpreting indicator are newly developed, feasible, proficient, and advanced, with a total of 2 students who have reached the indicator. 5) The science process skill of inferring indicator is newly developed, feasible, proficient, and advanced, with a total of 4 students who have reached the indicator. 6) The science process skills of the communicating indicator are newly developed, feasible, and proficient, with 2 students who have reached the indicator. The results of this study can be used as a reference to determine the science process skills possessed by students in learning.